Studi Empiris: Return On Assets, Debt To Equity Rasio Dan Return On Equity Terhadap Harga Saham Perusahaan Sub Sektor Pertambangan Batu Bara - Kurniawan, Raji; Fenisa, Delta; Sumaryanti, Atin (Accounting Global Journal, 2024)
The purpose of this study was to analyze the effect of return on assets, Debt to Equity Ratio, and Return on Equity on the share price of coal mining sub-sector companies listed on the IDX in 2019-2022. Quantitative research with an associative approach and the population used is coal mining sub-sector companies in 2019-2022 totaling 25 companies, and the sample obtained was 13 companies using purposive sampling technique, the analysis was carried out by multiple linear regression using SPSS version 24. The results showed that Return on Assets had no significant effect on stock prices, Debt to Equity Ratio had a negative and significant effect on stock prices, and Return on Equity had a positive and significant effect on stock prices.